Distribution. W, C & N Europe and N in Cricetidae - Don E. Wilson; Russell A. Mittermeier; Thomas E. Lacher, Jr (Lynx Edicions, 2017)
Distribution. W, C & N Europe and N Asia, from the British Is and across C & E Europe (including the Carpathian Basin) and Fennoscandia to Siberia as far E as Lena River, S to NE Kazakhstan, N Mongolia, and extreme NW China (Altai and Barluk Mts in Xinjiang). Published as part of Don E. Wilson, Russell A. Mittermeier & Thomas E. Lacher, Jr, 2017, Cricetidae, pp. 204-535 in Handbook of the Mammals of the World – Volume 7 Rodents II, Barcelona :Lynx Edicions on page 332, DOI: 10.5281/zenodo.6707142